La muy leal noble ciudad Iloilo city in the eyes of its large-scale business operators - Estrada, Aidy Esmao
This study was undertaken to identify and describe the large scale business operators, the reasons in establishing their business, plans for their business and vision for the city, and how they perceive Iloilo City. The 17 large-scale business operators residing in Iloilo City were chosen as respondents through purposive sampling that was based on the criteria set by the researchers. This study showed that for the large-scale business operators City is favorable place for business operation. Only that, cooperation should be practiced among the government, business sector and local residents.